A Study of Curriculum Development Models in Vocational Health Higher Education to Support an Impactful Campus for Polytechnic Students - Purnomo Ananto; Benget Simamora; Marcel Haggai (Ilomata International Journal of Social Science, 2026)
Curriculum development in vocational higher education continues to face structural challenges, particularly in aligning institutional design with dynamic labor market demands in the health sector. While existing studies emphasize competency-based and industry-oriented curricula, there remains a critical gap in empirically grounded, student-informed frameworks that integrate learning conditions, work–study balance, and adaptability to curricular change. This study addresses this gap by proposing a needs-informed curriculum development model derived from student experience, with an emphasis on adaptive learning environments and meaningful campus engagement. A quantitative descriptive approach was employed through a survey of 54 health polytechnic students. The study examined learning engagement, work–study conditions, and perceptions of curriculum implementation. The findings reveal that 72% of respondents were engaged in simultaneous work and study activities, while 68% reported achieving adequate mastery of theoretical knowledge and practical skills. However, 41% experienced moderate difficulties in adapting to curriculum changes, particularly in time management and instructional adjustment. These findings indicate that although dual-role students demonstrate resilience, structural support remains necessary to optimize learning outcomes. Based on these results, the study proposes a curriculum development model comprising three core components: (1) flexible curriculum structures accommodating working students, (2) adaptive learning strategies facilitating curriculum transition, and (3) experiential learning integration to enhance field relevance. The study implies that effective curriculum design in health polytechnics must extend beyond competency alignment to incorporate student adaptability and contextual learning dynamics. This research contributes a student-centered, empirically validated framework that strengthens institutional responsiveness and supports sustainable curriculum innovation.